Incidence of Match Injuries in an Amateur Women’s Rugby Union Team in New Zealand Over Two Consecutive Seasons - King, D; Hume, P; Clark, TN; Foskett, A; Barnes, M (Kosmos Publishers, 2020)
Background: Rugby Union is played in over 200 countries with over 8.5 million registered players worldwide. Despite increased popularity of the game for women, there is relatively little evidence for incidence, causes or severity of injuries that occur during match participation. Purpose: To determine whether amateur women’s rugby union teams in New Zealand need injury prevention support, by providing evidence as to the incidence, causes and severity of injuries that occur during match participation. Study design: Descriptive epidemiological observational study. Methods: Epidemiology analysis to describe the incidence of match injuries in an amateur women’s rugby union team in New Zealand, over two consecutive seasons. Injury burden was calculated for all injuries by: injury region, reported as frequency of injuries by region; number of days lost; and mean number of days lost, with standard deviation. Results: Over the study, 138 injuries were recorded resulting in an injury incidence of 247.0 per 1,000 match-hrs. A total of 57 resulted in a time-loss injury incidence of 102.0 per 1,000 match-hrs. The hooker recorded a significantly lower mean (4.1 ±2.8 days) injury burden than the blind-side flanker (t(6)=-2.8; p=0.0314), center (t(6)=-2.8; p=0.0313) and fullback (t(6)=-2.7; p=0.0351) for total injuries. Discussion: The principal findings of this study were: (1) total injury incidence was 247.0 per 1,000 match-hrs; (2) time-lost from rugby due to injuries was 102.0 per 1,000 match-hrs; (3) the lower limb sustained the highest injury incidence with the knee having the greatest proportion of these injuries; (4) the tackle recorded the highest injury rate, and being tackled was associated with a notably higher injury incidence than any other match event; (5) sprains and strains recorded the highest injury incidence; and (6) the lower limb body region recorded the most days lost and had the highest mean days lost per injury.
Keywords: Injuries; Injury-burden; Rugby; Women